Identification and Characterization of Lactic Acid Bacteria in a Commercial Probiotic Culture - MENCONI, Anita (Bioscience of Microbiota, Food and Health, 2014)
The aim of the present study was to describe the identification and characterization (physiological properties) of two strains of lactic acid bacteria (LAB 18 and 48) present in a commercial probiotic culture, FloraMax(®)-B11. Isolates were characterized morphologically, and identified biochemically. In addition, the MIDI System ID, the Biolog ID System, and 16S rRNA sequence analyses for identification of LAB 18 and LAB 48 strains were used to compare the identification results. Tolerance and resistance to acidic pH, high osmotic concentration of NaCl, and bile salts were tested in broth medium. In vitro assessment of antimicrobial activity against enteropathogenic bacteria and susceptibility to antibiotics were also tested. The results obtained in this study showed tolerance of LAB 18 and LAB 48 to pH 3.0, 6.5% NaCl and a high bile salt concentration (0.6%). Both strains evaluated showed in vitro antibacterial activity against Salmonella enterica serovar Enteritidis, Escherichia coli (O157:H7), and Campylobacter jejuni. These are important characteristics of lactic acid bacteria that should be evaluated when selecting strains to be used as probiotics. Antimicrobial activity of these effective isolates may contribute to efficacy, possibly by direct antimicrobial activity in vivo.